2002
DOI: 10.1136/sti.78.3.215
|View full text |Cite
|
Sign up to set email alerts
|

Risk factors for genital HPV DNA in men resemble those found in women: a study of male attendees at a Danish STD clinic

Abstract: Objectives: Genital infection with certain types of human papillomavirus (HPV) is the most important risk factor for cervical cancer. The male sexual partner is supposed to be the vector of the infection. However, the knowledge of risk factors for genital HPV DNA in men is limited. The objective of this paper is to study the risk factors for HPV infection in men and to compare them with those found in women, including the study of whether there are different risk profiles for oncogenic and non-oncogenic HPV ty… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

20
120
4
12

Year Published

2003
2003
2018
2018

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 157 publications
(156 citation statements)
references
References 15 publications
20
120
4
12
Order By: Relevance
“…9,13,14,17 In the study of Mexican soldiers, for instance, the OR for HPV positivity among men who reported a number of lifetime sexual partners over 5 vs. 1 was only 1.3 (nonsignificant). 17 As already noted, 24 the apparent association of HPV positivity with sexual behavior tends to weaken in studies of high-risk populations or subpopulations where the background prevalence of HPV is very high.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…9,13,14,17 In the study of Mexican soldiers, for instance, the OR for HPV positivity among men who reported a number of lifetime sexual partners over 5 vs. 1 was only 1.3 (nonsignificant). 17 As already noted, 24 the apparent association of HPV positivity with sexual behavior tends to weaken in studies of high-risk populations or subpopulations where the background prevalence of HPV is very high.…”
Section: Discussionmentioning
confidence: 99%
“…9,10 However, contrary to the relatively large amount of information on genital HPV infection in women, 2,11 large studies on HPV prevalence in the general male population are few. Furthermore, the majority of studies in men have focused on young individuals 12 or high-risk populations [e.g., men attending sexually transmitted disease (STD) clinics 9,13,14 or enrolled in military service [15][16][17].…”
mentioning
confidence: 99%
“…In STD clinics in Greenland and Denmark, HPV prevalence among men was 45%-49%, whereas, in a Swedish STD clinic, HPV prevalence was 13% [12,29,30]. In an international case-control study that investigated the HPV prevalence among the male partners of women with and without cervical cancer, International Agency for Research on Cancer (IARC) investigators found penile HPV DNA in 3.5%-39.0% of the control husbands and 12.0%-36.0% of husbands of the case patients, with prevalence varying significantly by country [15,16].…”
Section: Discussionmentioning
confidence: 99%
“…Factores de riesgo asociados de manera directa con infecciones por VPH BR son juventud del individuo, historia o presencia de verrugas genitales y número de parejas sexuales 15,17 .…”
Section: N V E S T I G a C I ó Nunclassified
“…Las técnicas de PCR presentan ventajas frente a la CH II, ya que puede identificar tipos específicos de VPH y diferenciar infecciones por VPH de AR y BR 12 . Para recolectar las células exfoliadas se han utilizado tórulas de algodón, cepillos y papeles abrasivos [13][14][15][16][17] . Las muestras de orina se han usado, pero con resultados deficientes 18,19 .…”
unclassified